2002
DOI: 10.1159/000064760
|View full text |Cite
|
Sign up to set email alerts
|

Prepubertal Growth in Children with Long-Term Parenteral Nutrition

Abstract: In children who depend on long-term parenteral nutrition (PN), a major goal is to obtain optimal growth. The aim of this retrospective study was to analyze growth in children on long-term cyclic nocturnal home PN, over at least 8 years before puberty. Nine boys and 7 girls were studied. Their mean age at the time of study was 11 years with a mean PN duration of 10.5 (8.6–16.4) years. Diseases were short bowel syndrome (5), intractable diarrhea (4), chronic intestinal pseudo-obstruction (4) and long segment Hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
1
15
1
1
Order By: Relevance
“…This somewhat paradoxical finding is likely because additional nutrition support was provided to the smallest infants in an effort to fuel catch-up growth. In contrast to existing literature, 8,25,26 we did not find that weaning from PN was associated with of worsening growth patterns, but we note that our follow-up period was limited to the first 12 months of life.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This somewhat paradoxical finding is likely because additional nutrition support was provided to the smallest infants in an effort to fuel catch-up growth. In contrast to existing literature, 8,25,26 we did not find that weaning from PN was associated with of worsening growth patterns, but we note that our follow-up period was limited to the first 12 months of life.…”
Section: Discussioncontrasting
confidence: 99%
“…8,25,26 There has been less attention on growth patterns during the immediate time after the intestinal injury. This is a critical period to study, because undesirable effects on somatic growth may have lasting effect.…”
Section: Discussionmentioning
confidence: 99%
“…Possible explanations to this finding could be that adolescents are closer to their maximum height because of obvious age differences, and that they had more years with a normal intestinal function when compared with the PG. This finding is consistent with long-term follow-up studies, where they found that neonatal SBS might affect the final height of the individual (5,14).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have studied growth assessment of children with SBS and concluded that it is possible to achieve a normal growth under adequate nutritional support (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
“…Llama la atención el compromiso de talla que se identificó en el 53,3% de los pacientes, independiente del lugar de tratamiento. Esto podría deberse a un aporte inadecuado de nutrientes en las etapas iniciales de la patología o en momentos de crecimiento acelerado, o bien podría ser el resultado de suspensiones transitorias del soporte nutricional debido a pérdidas de acceso venoso por períodos variables en el transcurso de la enfermedad 24 .…”
Section: Artículo Originalunclassified